2018
DOI: 10.3892/mmr.2018.9606
|View full text |Cite
|
Sign up to set email alerts
|

Parkin deficiency elevates hepatic ischemia/reperfusion injury accompanying decreased mitochondrial autophagy, increased apoptosis, impaired DNA damage repair and altered cell cycle distribution

Abstract: Hepatic ischemia/reperfusion injury (HIRI) serves a causative role in postoperative hepatocyte death; however, the mechanisms underlying HIRI remain unclear. Mitochondrial autophagy, with apoptosis, cell cycle distribution and DNA damage repair, may be regarded as a regulatory factor post-HIRI. Parkin, a novel ubiquitin ligase, has been reported to increase mitochondrial autophagy and decrease apoptosis. However, the association between Parkin, mitochondrial autophagy and other regulatory factors in HIRI is un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…When reperfusion initiates, the reestablishment of the electron transfer chain and ATP synthesis in mitochondria enables autophagy to eliminate abnormal proteins and organelles that are produced during ischemia. Enhanced hepatic mitophagy is observed at the early stages of IR in both in vivo and in vitro models, which is associated with elevated cell death and aggregated liver injury [164][165][166]. However, the autophagy capacity also becomes impaired following prolonged ischemia, which may not be sufficient to eliminate the accumulated dysfunctional mitochondria.…”
Section: Mitophagy In Liver Ischemia/reperfusion Injurymentioning
confidence: 99%
“…When reperfusion initiates, the reestablishment of the electron transfer chain and ATP synthesis in mitochondria enables autophagy to eliminate abnormal proteins and organelles that are produced during ischemia. Enhanced hepatic mitophagy is observed at the early stages of IR in both in vivo and in vitro models, which is associated with elevated cell death and aggregated liver injury [164][165][166]. However, the autophagy capacity also becomes impaired following prolonged ischemia, which may not be sufficient to eliminate the accumulated dysfunctional mitochondria.…”
Section: Mitophagy In Liver Ischemia/reperfusion Injurymentioning
confidence: 99%
“…Bone marrow mesenchymal stem cell-derived hepatocyte-like cell Exosomes and ulinastatin have also been proven to reduce hepatocellular apoptosis by enhancing autophagy [26,27]. Reducing mitochondrial autophagy by knocking out PINK can increase hepatic I/RI [28]. Our study demonstrated that in SI/RI-induced secondary liver injury, RIPC increased the expression of autophagy-related proteins, such as LC3 and Beclin-1, and decreased hepatocellular apoptosis, as well as markers of liver injury.…”
Section: Discussionmentioning
confidence: 57%
“…Mitophagy was reported to promote the clearance of injured mitochondria and then attenuate cell death induced by HIRI. Ning et al (2018) demonstrated that parkin mediated mitochondrial autophagy was upregulated post-HIRI, leading to decreased hepatocyte death. However, parkin deficiency elevates HIRI by decreasing mitochondrial autophagy and increasing apoptosis.…”
Section: Discussionmentioning
confidence: 97%